Expressions for the Autocorrelation Function and Power Spectral Density of BOC Modulation Based on Convolution Operation. (5th June 2020) - Ma, Jiangang; Yang, Yikang; Li, Hengnian; Li, Jisheng
Abstract : We present universal expressions for the autocorrelation functions (ACFs) of the Binary Offset Carrier (BOC), Multiplexed BOC (MBOC), and Alternative BOC (AltBOC) modulations based on convolution operations. We also derive the expressions for the power spectrum densities (PSDs) of these modulations using the Fourier transform of their ACFs. The results obtained in this contribution are useful for Global Navigation Satellite System (GNSS) signal simulation, performance evaluation, and high-performance acquisition and tracking algorithm design. The derivation methods of the expressions for the ACFs are common and can be used to derive expressions for the ACFs of other BOC-based modulations.